Enhanced microwave absorption in partition walls using rice husk biomass composites - Norhayati Mohamad Noor; Hasnain Abdullah@Idris; Mohd Nasir Taib; Nurin Sabihah Shamshul Bahari; Linda Mohd Kasim; Azizah Ahmad; Nazirah Mohamat Kasim; Noor Azila Ismail; Nur Shafikah Rosli (Universitas Ahmad Dahlan, 2025)
Currently, electromagnetic pollution (EM) has shown adverse complications and resulted in very negative effects on human health. Therefore, developing efficient microwave absorbers to reduce EM is important. This study aims to produce an anti-microwave partition wall using a biomass composite, which is a combination of rice husk and palm oil fuel ash (POFA). The goal of this project is to produce a partition wall that can act as a microwave absorber and create a healthy and safe environment. The anti-microwave radiation partition wall is designed using rice husk, POFA, cement, water, aluminium, and gypsum board. The composition ratios tested were rice husk content (5% and 20%) and POFA content (25%, 35%, and 45%). This mixture is also supplemented with aluminum (0.5% and 3.0%). The Naval Research Laboratory (NRL) Arch free space method determines the reflectivity performance of anti-microwave partition walls in the frequency range from 1 GHz to 12 GHz. Observation shows that the anti-microwave radiation partition wall for prototype BR5 containing 5% rice husk, 25% POFA, and 0.5% aluminium has the best reflectivity performance.